Effects of Tele-Exercise on Body Composition, Lipid Profile, Mental Health, and SIRT1 Gene Expression in Obese Office Employees in Indonesia - Kuswari, Mury; Rimbawan, Rimbawan; Hardinsyah, Hardinsyah; Dewi, Mira; Gifari, Nazhif; Pamungkas, Rian Adi; Seprianto, Seprianto; Himarwan, Aditya; Putra, Felicia Kartawidjaja; Dijaya, Rendy; Subali, Dionysius (Media Gizi Indonesia, 2026)
Tele-exercise delivers remote physical activity programs via digital platforms, enhancing accessibility and adherence, making it a promising strategy to address obesity among workers. This study aimed to evaluate the effects of tele-exercise programs on body fat percentage, lipid profile, mental health measures and Sirtuin 1 (SIRT1) gene expression measured via venipuncture & RT-PCR in obese office employees. A total of 33 overweight or obese employees (male/female, 18-45 years old, Body Mass Index (BMI) 23-30 kg/m2) were randomly assigned to the strength (SE) group, strength-cardio (SC) group, and control (CT) group. The strength exercise protocol included core training, circuit training, High Intensity Interval Training (HIIT) and Tabata training; cardio exercise includes low-high impact aerobic exercises. Each group was given nutrition education, whereas the two intervention groups participated in tele-exercise three times/week for twelve weeks. Tele-exercise was delivered via ZOOM application. Mental health indicators were measured using the Depression Anxiety Stress Scale (DASS-42) questionnaire. Compliance levels between intervention groups did not differ significantly (p>0.05). There was a significant reduction in bodyweight in the SC group (p=0.046). Blood High Density Lipoprotein (HDL) levels increased only in the SC group (0.50 mg/dL), but decreased in the SE group and CT group. SIRT1 gene expression increased in SE and CT groups (2.39- and 5.33-fold, respectively), whereas a significant decrease was observed in the SC group (p=0.043). Only the SE group showed a significant reduction in stress level (p=0.03), with a decrease of 30.9%. Strength exercise intervention improves total cholesterol level by -19.09 mg/dL.